2021
DOI: 10.1186/s12875-021-01398-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physician volume and quality of care for older adults with dementia: a retrospective cohort study

Abstract: Background Some jurisdictions restrict primary care physicians’ daily patient volume to safeguard quality of care for complex patients. Our objective was to determine whether people with dementia receive lower-quality care if their primary care physician sees many patients daily. Methods Population-based retrospective cohort study using health administrative data from 100,256 community-living adults with dementia aged 66 years or older, and the 8,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In Germany, primary care physicians (PCP) play a central role in the healthcare delivery for dementia 8–10 . A recent study reported between eight and 15 primary care visits per year among people living with dementia 11 . In our study, we found that people living with dementia visited their PCP on average almost three times over a 3‐month observation period 12 .…”
Section: Introductionsupporting
confidence: 46%
See 1 more Smart Citation
“…In Germany, primary care physicians (PCP) play a central role in the healthcare delivery for dementia 8–10 . A recent study reported between eight and 15 primary care visits per year among people living with dementia 11 . In our study, we found that people living with dementia visited their PCP on average almost three times over a 3‐month observation period 12 .…”
Section: Introductionsupporting
confidence: 46%
“…[8][9][10] A recent study reported between eight and 15 primary care visits per year among people living with dementia. 11 In our study, we found that people living with dementia visited their PCP on average almost three times over a 3month observation period. 12 Despite empirical evidence highlighting the key role of PCP in dementia healthcare provision, past research has acknowledged challenges in primary care and dementia.…”
mentioning
confidence: 58%
“…Necessities of transitions of care to community physicians may further result in fragmentation of care [ 32 ]. Indeed, it has been shown that increased patient volume may have a detrimental impact on dialysis outcomes, re-admission rates, cost of care, as well on preventive care delivery [ 5 , 33 35 ]. Based upon the data from our study, where medium-high volume (Q3) centers achieved better outcomes, it is tempting to hypothesize that there may be a ‘sweet spot’ where one could derive the advantages of superior peri-operative care without compromising long-term care due to excessive patient volume.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cognitive impairment was similar to the observations of the few studies which already exists, which found the dementia rates ranging from 10% to 58.6% in OAHs. [ 6 15 16 17 18 19 20 ] The OAH group had greater rates of inadequate social support, whereas the community group had greater rates of great social support (8.3%). One of the studies found poor social support in OAH residents.…”
Section: Discussionmentioning
confidence: 99%